The impact of hearing impairment and noise-induced hearing injury on quality of life in the active-duty military population: challenges to the study of this issue. Issue 1 (December 2016) - Alamgir, Hasanat; Turner, Caryn; Wong, Nicole; Cooper, Sharon; Betancourt, Jose; Henry, James; Senchak, Andrew; Hammill, Tanisha; Packer, Mark
Abstract The objectives of this research were to 1) summarize the available evidence on the impact of hearing loss on quality of life (QOL) among U.S. active-duty service members, 2) describe the QOL instruments that have been used to quantify the impact of hearing loss on quality of life, 3) examine national population-level secondary databases and report on their utility for studying the impact of hearing loss on QOL among active-duty service members, and 4) provide recommendations for future studies that seek to quantify the impact of hearing loss in this population. There is a lack of literature that addresses the intersection of hearing impairment, the military population, and quality of life measures. For audiological research, U.S. military personnel offer a unique research population, as they are exposed to noise levels and blast environments that are highly unusual in civilian work settings and can serve as a model population for studying the impact on QOL associated with these conditions. Our team recommends conducting a study on the active-duty service member population using a measurement instrument suitable for determining decreases in QOL specifically due to hearing loss.